Barriers to seeking consultation at public service and medical facilities among pregnant and postpartum women in Japan: a cross-sectional study - Okawa, Sumiyo; Seino, Kaori; Iso, Hiroyasu; Tabuchi, Takahiro (PeerJ, 2025)
Background Pregnant and postpartum women often experience parenting problems which may affect their mental health and children’s health and development. However, their ability to seek consultation at public service or medical facilities remains unclear. This study aimed to identify the characteristics associated with women who refrain from visiting these facilities for consultation and their reasons for it. Methods This cross-sectional internet-based survey was conducted in Japan between July and August 2021, involving 7,326 women (1,639 pregnant and 5,687 postpartum women). The study outcome was defined as refraining from seeking consultation on family or parenting issues at public service or medical facilities despite a perceived need. We identified women’s characteristics associated with refraining from consultation using multivariable logistic regression and conducted a descriptive analysis of 13 listed reasons for refraining from the consultation. Results The percentage of women who reported refraining from seeking consultation at public service or medical facilities was 8.6% and 5.1%, respectively. Common factors associated with refraining from seeking consultation at these facilities included having a child(ren) and being in the postpartum period, low health literacy, lack of partner support, and current disability. “Difficulty taking child(ren) to the consultation” and “uncertainty about the seriousness of the problem” were major reasons for refraining from consultation. Discussion Healthcare workers at public service and medical facilities should offer prenatal education on the importance of seeking help. An online consultation service and an improved facility environment may mitigate women’s perceived barriers to seeking consultation.
Keywords: Care seeking; Help seeking; Parenting; Maternal health